Dromedary (Camelus dromedarius) and Bactrian camel (Camelus bactrianus) crossbreeding husbandry practices in Turkey and Kazakhstan: An in-depth review - Maurizio Dioli (Pastoralism, 2020)
Abstract Hybridization between dromedaries and Bactrian camels has been carried out since ancient times in various areas of the Middle East and Central Asia. The primary force behind such practice was to obtain a better pack camel for trade caravans and military interventions. Today, camel hybridization is carried out systematically in only two areas: Turkey and Kazakhstan. In Turkey, camel cross-breeding is mainly done to obtain large animals for the annual camel wrestling competitions, while in Kazakhstan, cross-breeding is done to obtain camels that are more productive and better able to resist the harsh climate of Central Asia.